2020
DOI: 10.1111/avj.13015
|View full text |Cite
|
Sign up to set email alerts
|

Introduction and elimination of Bovine Viral Diarrhoea Virus in a commercial beef herd: a case study

Abstract: Routine Bovine Viral Diarrhoea Virus (BVDV) monitoring of a commercial beef herd in southern New South Wales over a 10-year period provided an opportunity to assess the impact of the introduction of BVDV on that herd. BVDV antibody testing provided strong evidence that the herd was initially free of BVDV (2009-2011). Testing from 2012 suggested BVDV had been introduced into the herd and this was confirmed in 2015 with the identification of persistently infected (PI) animals. Having become established in the he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 20 publications
3
4
0
Order By: Relevance
“…Apart from undetected losses, difficulty in communicating the negative impacts of BVDV to stakeholders is partly due to the wide variation in outcomes that could occur during an outbreak of BVDV. Poor conception and reduced pregnancy risks are often identified during BVDV outbreaks ( 70 ); however, this study, consistent with Allworth et al ( 65 ), found that the pregnancy risk in a herd of 400 animals was largely unaffected by BVDV. The joining practices used in this model and described by Allworth et al ( 65 ) are similar to industry-recommended joining practices for seasonal calving beef herds in NSW (McConchie 2007, MLA 2019).…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Apart from undetected losses, difficulty in communicating the negative impacts of BVDV to stakeholders is partly due to the wide variation in outcomes that could occur during an outbreak of BVDV. Poor conception and reduced pregnancy risks are often identified during BVDV outbreaks ( 70 ); however, this study, consistent with Allworth et al ( 65 ), found that the pregnancy risk in a herd of 400 animals was largely unaffected by BVDV. The joining practices used in this model and described by Allworth et al ( 65 ) are similar to industry-recommended joining practices for seasonal calving beef herds in NSW (McConchie 2007, MLA 2019).…”
Section: Discussionsupporting
confidence: 88%
“…Poor conception and reduced pregnancy risks are often identified during BVDV outbreaks ( 70 ); however, this study, consistent with Allworth et al ( 65 ), found that the pregnancy risk in a herd of 400 animals was largely unaffected by BVDV. The joining practices used in this model and described by Allworth et al ( 65 ) are similar to industry-recommended joining practices for seasonal calving beef herds in NSW (McConchie 2007, MLA 2019). These short duration joining periods are designed to limit infertility and might also reduce the apparent reproductive effects of BVDV infection.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations